2006
DOI: 10.1007/s00192-006-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of stress urinary incontinence among women in Turkey

Abstract: The aim of this study was to determine the incidence of stress urinary incontinence among women at the age of 15 and above who applied to the primary health care centers in Ankara, Turkey. We applied the urinary stress incontinence questionnaire to 2,601 women at the age of 15 or above who consulted to the "mother-child health care and family planning centers" in January 2002. To evaluate the urinary incontinence status with respect to age groups and other risk factors, chi-square test was used. Stress inconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
6
21
2
9
Order By: Relevance
“…Only 12.4%-27.7% of women in Turkey seek medical aid for UI, even though it negatively affects their life quality (5,18). In the metaanalysis study conducted by Minassian et al the researchers found that 31%-42% of women sought medical aid (27).…”
Section: Discussionmentioning
confidence: 99%
“…Only 12.4%-27.7% of women in Turkey seek medical aid for UI, even though it negatively affects their life quality (5,18). In the metaanalysis study conducted by Minassian et al the researchers found that 31%-42% of women sought medical aid (27).…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye'de kadınlarda SÜİ prevalansı 15-24 yaş arasında %4.7, 35-44 yaş arasında %21.6, 55-64 yaş arasında %25.1 ve 65 yaş üstünde %21.9 olarak bulunmuştur (2). SÜİ tedavisinde; üretro-vesikal bileşkeye hamak-benzeri destek sağlayan birçok cerrahi teknik tanımlanmış olmasına rağ-men, 2001 yılında dıştan-içe transobturator tape (TOT) operasyonunu tanımlamasından sonra; güvenilir, etkin ve minimal invazif bir teknik olarak yaygın şekilde kullanılmaya başlamıştır (3).…”
Section: Introductionunclassified
“…(23,24) . Ü‹ prevelans›n›n dünya popülasyonunda ortalama %17 ile %58.4 oran›nda oldu¤u tahmin edilmektedir (25)(26)(27) . Türkiye'de Ü‹ prevalans› %25.8 ile %68.8 aras›nda de¤iflmektedir (28)(29)(30) .…”
Section: Kad›n Cinsel Disfonksiyonu Ve Prevalans›unclassified